Analisis Node dengan Centrality dan Follower Rank pada Twitter - Evangs Mailoa (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Twitter is used to express about something that happened. In Indonesia since 2012, Twitter has been widely used for campaigns during regional or presidential elections. Apart from positive campaigns, negative campaigns and even black campaigns were carried out via Twitter, and tweets become twitwar. Twitter is a social network, so the data can be analyzed using a social network analysis approach. This research was conducted to analyze which nodes (actors) are influential using the degree, between, and closeness centrality methods, while the follower rank method is used for the analysis of popular actors in 4niesKingOfDrama